Role of N in Transition‐Metal‐Nitrides for Anchoring Platinum‐Group Metal Atoms toward Single‐Atom Catalysis. Issue 7 (8th June 2022) - Ma, Mingyu; Cheng, Xu; Shi, Zude; Zhang, Chenglan; Li, Yan; Yang, Yifan; Gong, Chengshi; Zhang, Zhenxing; Fei, Huilong; Zhu, Chao; He, Yongmin; Xie, Erqing
Abstract: Single‐atom catalysts (SACs) with a maximum atom utilization efficiency have received growing attention in heterogeneous catalysis. The supporting substrate that provides atomic‐dispersed anchoring sites and the local electronic environment in these catalysts is crucial to their activity and stability. Here, inspired by N‐doped graphene substrate, the role of N is explored in transition metal nitrides for anchoring single metal atoms toward single‐atom catalysis. A pore‐rich metallic vanadium nitride (VN) nanosheet is fabricated as one supporting‐substrate example, whose surface features abundant unsaturated N sites with lower binding energy than that of widely used N‐doped graphene. Impressively, it is found that this support can anchor nearly all platinum‐group single atoms (e.g., platinum, palladium, iridium, and ruthenium), and even be extendable to multiple SACs, i.e., binary (Pt/Pd) and ternary (Pt/Pd/Ir). As a proof‐of‐concept application for hydrogen production, Pt‐based SAC (Pt1 ‐VN) performs excellently, exhibiting a mass activity up to 22.55 A mg −1 Pt at 0.05 V and a high turnover frequency value close to 0.350 H2 s −1, superior to commercial platinum/carbon catalyst. The catalyst's durability can be further improved by using binary (Pt1 Pd1 ‐VN) SAC. This work provides inexpensive and durable nitride‐based support, giving a possible pathway for universally constructing platinum‐group SACs. Abstract : In this work, the vanadium nitride support as an example was investigated to reveal the role of nitrogen chemistry for anchoring behavior for single platinum‐group metal atoms. As a proof‐of‐concept for hydrogen generation, the platinum‐based single‐atom catalyst shows an onset overpotential of 43.7 mV and a mass activity of 22.55 A mg −1 Pt, superior to commercial platinum/carbon catalysts.